2013
DOI: 10.1093/mnras/stt1027
|View full text |Cite
|
Sign up to set email alerts
|

The supermassive black hole mass–Sérsic index relations for bulges and elliptical galaxies

Abstract: Scaling relations between supermassive black hole mass, M BH , and host galaxy properties are a powerful instrument for studying their coevolution. A complete picture involving all of the black hole scaling relations, in which each relation is consistent with the others, is necessary to fully understand the black hole-galaxy connection. The relation between M BH and the central light concentration of the surrounding bulge, quantified by the Sérsic index n, may be one of the simplest and strongest such relation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 59 publications
6
80
1
Order By: Relevance
“…Indeed, one migh expect that a Sérsic index measured using a onedimensional fit (as performed in this paper) to be ∼10% smaller than that measured using a two-dimensional fit (Ferrari et al 2004). Furthermore, when measuring Sérsic index in multiple wavebands for the same galaxies, Savorgnan et al (2013) found that wavelength bias was completely dominated by these other biases, which could be as large as 50%. Given, the result of Kelvin et al (2012), we would expect the Sérsic index measured at 3.6µmto be less than 10% higher than that measured in the R-band, which is signifantly smaller than the 50% number given by Savorgnan et al (2013).…”
Section: Bh -P Relation and M Bh -N Relationmentioning
confidence: 58%
See 2 more Smart Citations
“…Indeed, one migh expect that a Sérsic index measured using a onedimensional fit (as performed in this paper) to be ∼10% smaller than that measured using a two-dimensional fit (Ferrari et al 2004). Furthermore, when measuring Sérsic index in multiple wavebands for the same galaxies, Savorgnan et al (2013) found that wavelength bias was completely dominated by these other biases, which could be as large as 50%. Given, the result of Kelvin et al (2012), we would expect the Sérsic index measured at 3.6µmto be less than 10% higher than that measured in the R-band, which is signifantly smaller than the 50% number given by Savorgnan et al (2013).…”
Section: Bh -P Relation and M Bh -N Relationmentioning
confidence: 58%
“…Recently, Sani et al (2011), Vika et al (2012 and Beifiori et al (2012) failed to recover a strong M bhn relation. Savorgnan et al (2013) re-investigated and recovered the relation using a large collection of literature Sérsic index measurements using R-band , I-band (Beifiori et al 2012), K-band (Vika et al 2012), and 3.6µm (Sani et al 2011) imaging data. Savorgnan et al (2013) discussed the systematic effects associated with measuring Sérsic index in different optical and infrared wavebands.…”
Section: Bh -P Relation and M Bh -N Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sérsic indices of bulges are also important, as they provide a link to their supermassive black hole. Following on the work of Graham et al (2001) and Graham & Driver (2007a), recent work by Savorgnan et al (2013) found a clear supermassive black-hole mass − Sérsic index relation. Thus, if accurate Sérsic indices can be derived (corrected for the effect of dust and for projection effects), then these can be used to predict black hole masses in large samples of galaxies to derive the local black hole mass function (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…Tight correlations between the mass of the central supermassive black hole (SMBH) and properties of the hosting galaxy, particularly its central bulge component, have been found (Magorrian et al 1998;Ferrarese & Merritt 2000;Marconi & Hunt 2003;Häring & Rix 2004;Graham & Driver 2007;Savorgnan et al 2013) and are seen as evidence of a co-evolution of black holes and their host galaxies. More recent studies have revealed galaxies that do not follow these relations: Kormendy et al (2011) discuss that only "classical bulges" that formed from galaxy mergers show correlations with the SMBH, while disklike "pseudobulges" that are forming by secular evolution do not.…”
Section: Introductionmentioning
confidence: 99%